Neuroendoscopic evacuation of intraventricular empyema using a side-cutting aspiration device. (January 2018) - Lang, Min; Habboub, Ghaith; Moore, Nina Z.; Recinos, Violette M.R.; Mohammadi, Alireza M.; Nagel, Sean; Bhimraj, Adarsh; Silva, Danilo; Recinos, Pablo F.
Highlights: Intravenous and intrathecal antibiotics are sometimes inadequate to treat pyogenic ventriculitis. Neuroendoscopic approach is useful for removing intraventricular pus when antibiotics alone are insufficient. The utilization of a side-cutting aspiration device appears especially useful for removing adherent intraventricular empyema that is nonresponsive to antibiotics. Abstract: Pyogenic ventriculitis is a rare but severe post-neurosurgical complication. The infection is often resistant to antibiotic treatment alone. Continuous intraventricular irrigation has been suggested but the technique is cumbersome, increases the risk for secondary infection, and is inadequate in removing adherent purulence. We used a novel neuroendoscopic approach assisted with a side-cutting aspiration device to treat four cases of post-neurosurgical pyogenic ventriculitis. Ventricular empyema was cleared in all patients and three of the four patients had favorable outcomes.